Caminhos para o poder: a seleção de candidatos a Deputado Federal nas eleições de 2010 - Bolognesi, Bruno (Universidade Federal de São Carlos, 2013)
The main purpose in this thesis is to analyse the candidate selection process for Federal Deputy in Brazil in the 2010 elections within four parties: DEM, PMDB, PSDB e PT. Heretofore, the study of candidate selection in our country have privileged the formal dimension of selection, like party´s statutes analysis or regional dinamics. In the other hand, except for some exceptions, the conclusions pointed out the impact of brazilian institutional design in candidate selection, undervaluing parties as autonomus units in the process. Therefore, from data about candidacy gathered at the Electoral Supreme Court and a survey applied to one hundred and twenty candidates, we tried to sketch the candidate selection process at the intra-party arena. The conclusions suggests that political parties are capable in divert from institucional incentives and choose candidates by different methods regarding the strenght and direction of the institutionalization. Hence, the different methods bring relevant consequences for the candidates profiles as well for the parties themselves.
Keywords: Ciência política; Seleção de candidatos; Partidos políticos; Recrutamento político; Organização partidária; Institucionalização partidária; Candidate selection; Political parties; Political recruitment; Party institutionalization; Party organization; CIENCIAS HUMANAS::CIENCIA POLITICA